2022
DOI: 10.1126/sciadv.abj8633
|View full text |Cite
|
Sign up to set email alerts
|

Cln5 represents a new type of cysteine-based S -depalmitoylase linked to neurodegeneration

Abstract: Genetic CLN5 variants are associated with childhood neurodegeneration and Alzheimer’s disease; however, the molecular function of ceroid lipofuscinosis neuronal protein 5 (Cln5) is unknown. We solved the Cln5 crystal structure and identified a region homologous to the catalytic domain of members of the N1pC/P60 superfamily of papain-like enzymes. However, we observed no protease activity for Cln5; and instead, we discovered that Cln5 and structurally related PPPDE1 and PPPDE2 have effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…A recent study suggested regulation of S-depalmitoylation through palmitoyl thioesterase activity, leading to impairment in assembly and compartmentalisation of neuronal proteins and consequently affecting neuronal development. Variants affecting the palmitate binding pocket or the active site cause loss of thioesterase activity,3 but this putative mechanism does not explain the pathogenicity of most reported variants, including the p.Arg63Cys variant reported here.…”
mentioning
confidence: 55%
“…A recent study suggested regulation of S-depalmitoylation through palmitoyl thioesterase activity, leading to impairment in assembly and compartmentalisation of neuronal proteins and consequently affecting neuronal development. Variants affecting the palmitate binding pocket or the active site cause loss of thioesterase activity,3 but this putative mechanism does not explain the pathogenicity of most reported variants, including the p.Arg63Cys variant reported here.…”
mentioning
confidence: 55%
“…These findings are consistent with work in D. discoideum and mammalian models of CLN5 disease that have linked the function of CLN5 to these cellular processes ( El Haddad et al, 2012 ; Schmiedt et al, 2012 ; Best et al, 2017 ; Leinonen et al, 2017 ; Adams et al, 2019 ; Doccini et al, 2020 ; McLaren et al, 2021 ; Yasa et al, 2021 ; Doccini et al, 2022 ). Previous work suggests that CLN5 functions as either a glycoside hydrolase or depalmitoylase ( Huber and Mathavarajah, 2018a ; Luebben et al, 2022 ). Here, comparative transcriptomics showed that loss of cln5 during growth alters the expression of genes that encode enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in CLN5 cause the CLN5 disease subtype of NCL (Schulz et a., 2013; Mole and Cotman, 2015 ). CLN5 is a soluble lysosomal and extracellular protein that is predicted to function as either a glycoside hydrolase or depalmitoylase ( Isosomppi et al, 2002 ; Hughes et al, 2014 ; Jules et al, 2017 ; Huber and Mathavarajah, 2018a ; Basak et al, 2021b ; Luebben et al, 2022 ). CLN5 has been linked to several cellular processes including, but not limited to, endosomal sorting, biometal homeostasis, sphingolipid metabolism, and autophagy ( El Haddad et al, 2012 ; Mamo et al, 2012 ; Grubman et al, 2014 ; Doccini et al, 2020 ; McLaren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, thirteen CLN proteins have been identified and characterized (PPT1/CLN1, TPP1/CLN2, CLN3, DNAJC5/CLN4, CLN5, CLN6, MFSD8/CLN7, CLN8, CTSD/CLN10, GRN/CLN11, ATP13A2/CLN12, CTSF/CLN13, KCTD7/CLN14) (Figure 1) (Butz et al, 2020; Mole & Cotman, 2015). Palmitoyl protein thioesterase 1 (PPT1), tripeptidyl peptidase 1 (TPP1), ceroid lipofuscinosis neuronal 5 (CLN5), cathepsin D (CTSD), and cathepsin F (CTSF) localize to lysosomes and function as soluble enzymes (Barrett, 1967; Hofmann et al, 1997; Huber & Mathavarajah, 2018; Isosomppi et al, 2002; Jerič et al, 2013; Luebben et al, 2022; Passini et al, 2006). They have also been detected extracellularly hinting that they may also play essential roles outside cells (Huber, 2021; Hughes et al, 2014; Isosomppi et al, 2002; Kaakinen et al, 2007; Kohan et al, 2005; Oörni et al, 2004; Poole et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests CLN proteins have shared functions, regulate similar processes, and participate in shared or convergent biological pathways (Huber, 2020). For example, both PPT1 and CLN5 have been reported to have depalmitoylase activity (PPT1: palmitoyl thioesterase, family of alpha/beta‐serine hydrolases; CLN5: cysteine‐based S‐depalmitoylase) (Cho et al, 2000; Luebben et al, 2022). In addition, significant overlap was detected in CLN3, CLN6, and CLN8 protein interactomes from mouse Neuro2A cells (Rechtzigel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%